Collision detection for six-DOF serial robots force/position hybrid control based on continuous friction model. (March 2023) - Zhang, Chuntao; Mu, Chunyang; Wang, Yong; Li, Jiawang; Liu, Zhengshi
In this work, an effective and practical robot collision detection algorithm is proposed, with the aim of addressing the safety problem of industrial robot force/position hybrid control application conditions. First, a robot force/position hybrid control collision detection scheme was designed, and a collision detection model based on dynamics was established. Then, given the problem of large joint friction force identification error caused by the discontinuous joint speed of the robot force control, the continuous friction model was used to identify and address the joint friction problem through the least square method. Finally, experiments were carried out on a light industrial manipulator. According to the different collision directions of the robots during the experiment, a collision detection method was proposed to monitor the torque changes of the position control joints and the force control joints. Experimental results prove that the continuous friction model is more accurate and effective for joint friction compensation than other methods. The proposed method can achieve effective collision detection with force and position control direction thresholds of 8 and 4 N·m, respectively. The practicability and simplicity of the algorithm that can streamline the process of robot collision detection, the simplified model of the collision detection process only detects the torque change in the position control direction, which has a certain engineering reference value.